IMPLEMENTATION OF ISLAMIC GUIDANCE AND COUNSELING IN PANCA BUDI MEDAN PRIVATE JUNIOR HIGH SCHOOL - Akhyar, Saiful; Lubis, Lahmuddin; Suriani, Erna Suriani (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
The purpose of this research is to know, explain and interpret how the implementation of Islamic Counseling in Smp Swasta Panca Budi Medan starts from program planning, organizing, implementation and supervision and explaining supporting factors and inhibition of the program. This type of research used in this dissertation uses qualitative research. The primary data is data collected through interviews with the Principal of SMP Panca Budi, Vice Principals, Counseling Guidance Teachers, homeroom teachers, parents of students, and students of Panca Budi Private Junior High School. The secondary data is supporting data, such as references relevant to the topics being researched both from books and journals of relevant research results. The implementation of Islamic Counseling at Smp Swasta Panca Budi Medan has been well implemented by the principal of SMP Panca Budi. The first step is to plan the Implementation of Islamic Counseling which includes the preparation of programs, implementors, budgets, places, and others. The next step is to organize the Implementation of Islamic Counseling at Smp Swasta Panca Budi Medan by appointing Islamic counseling guidance teachers as implementers, and homeroom teachers, and another field of study teachers who participated in the successful implementation of Islamic counseling guidance at SMP Panca Budi Medan.